Higher Pericyte Content and Secretory Activity of Microfragmented Human Adipose Tissue Compared to Enzymatically Derived Stromal Vascular Fraction. (26th September 2018) - Vezzani, Bianca; Shaw, Isaac; Lesme, Hanna; Yong, Li; Khan, Nusrat; Tremolada, Carlo; Péault, Bruno
Abstract : Autologous adipose tissue is used for tissue repletion and/or regeneration as an intact lipoaspirate or as enzymatically derived stromal vascular fraction (SVF), which may be first cultured into mesenchymal stem cells (MSCs). Alternatively, transplant of autologous adipose tissue mechanically fragmented into submillimeter clusters has recently showed remarkable efficacy in diverse therapeutic indications. To document the biologic basis of the regenerative potential of microfragmented adipose tissue, we first analyzed the distribution of perivascular presumptive MSCs in adipose tissue processed with the Lipogems technology, observing a significant enrichment in pericytes, at the expense of adventitial cells, as compared to isogenic enzymatically processed lipoaspirates. The importance of MSCs as trophic and immunomodulatory cells, due to the secretion of specific factors, has been described. Therefore, we investigated protein secretion by cultured adipose tissue clusters or enzymatically derived SVF using secretome arrays. In culture, microfragmented adipose tissue releases many more growth factors and cytokines involved in tissue repair and regeneration, noticeably via angiogenesis, compared to isogenic SVF. Therefore, we suggest that the efficient tissue repair/regeneration observed after transplantation of microfragmented adipose tissue is due to the secretory ability of the intact perivascular niche.